2016
DOI: 10.1002/2015wr017290
|View full text |Cite
|
Sign up to set email alerts
|

Vertically integrated models for coupled two‐phase flow and geomechanics in porous media

Abstract: Models of reduced dimensionality have been found to be particularly attractive in simulating the fate of injected CO 2 in supercritical state in the context of carbon capture and storage. This is motivated by the confluence of three aspects: the strong buoyant segregation of the lighter CO 2 phase above water, the relatively long time scales associated with storage, and finally the large aspect ratios that characterize the geometry of typical storage aquifers. However, to date, these models have been confined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…While our derivation is different, our mixed-dimensional equations coincide in the case of a single thin inclusion with the elastic equations derived in [7]. In that work, significant effort was placed into model verification, including comparison to fixed-dimensional models.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…While our derivation is different, our mixed-dimensional equations coincide in the case of a single thin inclusion with the elastic equations derived in [7]. In that work, significant effort was placed into model verification, including comparison to fixed-dimensional models.…”
Section: Introductionmentioning
confidence: 82%
“…The governing equations on this manifold can be derived using vertical integration [22]; see e.g. [7] for an application regarding CO 2 storage.…”
Section: Introductionmentioning
confidence: 99%
“…The VE assumption was found to be valid in the limit of large R 2 L . In a validation model presented by Bjørnarå et al [25] based on realistic CO 2 storage conditions at In Salah, Algeria, it was found that it holds even for reservoir thickness H up to at least 100 meters. The VEassumption implies further that since the pressure is in vertical equilibrium, then so is the phase distribution, or saturation.…”
Section: Dimensionally Reduced Modelsmentioning
confidence: 98%
“…Over time, the capabilities of such tools have been expanded to account for a considerable range of physical phenomena [27,16,17,26,1]. However, reduced models that properly account for the twoway coupling between fluid flow and rock mechanics have so far received less attention, although recent work in this field includes the linear vertical deflection model of [5].…”
Section: Introductionmentioning
confidence: 99%
“…At the theoretical level, the poromechanical framework has been used to investigate the risk of fracturing or fault slip caused by elevated pressure and reduced effective stress [34,32,6], and assess the risk of induced seismicity [7]. A reduced model for coupled flow and geomechanics, adapted to the case of CO 2 storage, was proposed by [5], whereas [9] situates geomechanics within a comprehensive modeling framework for CO 2 storage, where different physical processes are modeled depending on the spatial and temporal scale. Specific case-studies involving CO 2 injection and geomechanical impacts include Ketzin [29], In-Salah [35,30,4], Vedsted [39] and the CO2CRC Otway Project [2].…”
Section: Introductionmentioning
confidence: 99%